2007
DOI: 10.1016/j.clnu.2007.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue arachidonic acid and the metabolic syndrome in Costa Rican adults

Abstract: Background & Aims-Arachidonic acid, a precursor to a series of inflammatory mediators, may contribute to the development of insulin resistance. We examined the association between adipose tissue arachidonic acid and the metabolic syndrome in Costa Rica, a country in which the metabolic syndrome is highly prevalent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 38 publications
4
29
0
Order By: Relevance
“…AA is a ω-6-PUFA and is the primary source of fatty acids that mediate inflammatory responses [9]. Elevated tissue levels of AA have been associated with a number of disease states, including coronary heart disease, breast cancer, obesity and diabetes [38]. A recent study has associated increased AA levels in retroperitoneal AT with a high prevalence of the metabolic syndrome in human subjects [38].…”
Section: Discussionmentioning
confidence: 99%
“…AA is a ω-6-PUFA and is the primary source of fatty acids that mediate inflammatory responses [9]. Elevated tissue levels of AA have been associated with a number of disease states, including coronary heart disease, breast cancer, obesity and diabetes [38]. A recent study has associated increased AA levels in retroperitoneal AT with a high prevalence of the metabolic syndrome in human subjects [38].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study assessing the relationship between AA and the presence of metabolic syndrome risk factors in a cohort of more than 480 normal and overweight Costa Rican adults found that adipose tissue AA content was associated with the presence of metabolic syndrome and was also independently associated with abdominal obesity, hypertriglyceridemia, and elevated fasting glucose when adjusted for BMI [117]. Similarly, a study conduct in a Spanish population found a correlation between the adipose tissue LA content (which also correlated with dietary LA intake), degree of obesity and central adiposity [118].…”
Section: Linoleic Acid and Obesity: Population Evidencementioning
confidence: 98%
“…For example, AA found in adipose tissue was found to be independently associated with MetS as well as abdominal obesity, hypertriglyceridemia, fasting glucose and blood pressure among adults [81].…”
Section: Lipids and Metabolic Syndromementioning
confidence: 99%